Some Legal Issues in Natural Resources’ International Management - E. V. Vasilenko (Московский журнал международного права)
The article examines the concept of international governance which is largely due to the efficiency of natural resources dispute settlement, supranational phenomenon in contemporary international law, formation and enrichment of the concept of sustainable development in light of the planned Conference on Sustainable Development in 2012. The author highlights the important issues in activities of international governmental organizations and international judicial institutions related to natural resources exploration, prospecting and exploitation.